2020
DOI: 10.1073/pnas.2020507117
|View full text |Cite
|
Sign up to set email alerts
|

A risk–benefit framework for human research during the COVID-19 pandemic

Abstract: The coronavirus disease 2019 (COVID-19) has had a profound impact on the academic research enterprise. Over the span of just a few weeks in March 2020, most large U.S. research institutions closed the majority of their laboratories, studios, and offices, suspended travel and fieldwork, and paused the majority of human research, resulting in the halt of more than 80% of all on-site research activity (1). After months of limited operations, laboratory-and field-based research in the basic and natural sciences we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…The COVID-19 pandemic changed the clinical research landscape in America [1]. IRB leaders at academic health centers knew their offices would have to respond to several challenges associated with this pandemic [2]. The most urgent challenge was to rapidly review protocols submitted by investigators that were designed to learn more about COVID-19.…”
Section: Introduction and Challengesmentioning
confidence: 99%
“…The COVID-19 pandemic changed the clinical research landscape in America [1]. IRB leaders at academic health centers knew their offices would have to respond to several challenges associated with this pandemic [2]. The most urgent challenge was to rapidly review protocols submitted by investigators that were designed to learn more about COVID-19.…”
Section: Introduction and Challengesmentioning
confidence: 99%
“…As far as research is concerned, significant challenges have been encountered in terms of the planning of clinical research designs, sourcing of funding for research as research priorities change, as well as significant questions around ethical clearance of studies conducted during the COVID-19 pandemic. Questions around ethical clearance have had ethical committees and institutional research review boards challenged by their mandate to facilitate ethical research whilst adhering to health and safety regulations implemented to protect and safeguard the safety of research participants and researchers (Beach et al, 2020 ; Lumeng et al, 2020 ; Perez et al, 2020 ; Sebothoma et al, 2021 ; Wieten, Burgart, & Cho, 2020 ). Weiner, Balasubramaniam, Shah and Javier ( 2020 ) believed that the impact that the COVID-19 pandemic had on general research and on research specific to the pandemic raises numerous important factors: (1) the significance of research, (2) challenges of research, especially during public health emergencies (PHEs) and (3) resources and opportunities towards improving research to become more efficient and cost effective.…”
Section: Introductionmentioning
confidence: 99%
“…The travel restrictions also impacted the access to research tools that are most often imported, particularly in LMICs. Lumeng et al ( 2020 ) further reported on how COVID-19 has had a significant effect on the academic research enterprise in the United States, with numerous research institutions shutting down their research laboratories, adjourning fieldwork and stopping a number of human research initiatives. This led to the cessation of over 80% of all on-site research activity – with research in the basic and natural sciences gradually resuming activities over the course of a few months (Lumeng et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is not possible to assure these first results reveal the real effects of interventions since current limitations and stress imposed on the participants can influence their outcomes. We have learned that the current global situation asks for additional phases in the Diabetes College Brazil Study to validate the results, including a feasibility RCT study with a virtual intervention 21 .…”
Section: Learning During Challenging Timesmentioning
confidence: 99%